An Ontological Perspective on the Development of Home–School Partnership Relationships with Indigenous Communities - Hindle, Rawiri; Hynds, Anne; Averill, Robin; Meyer, Luanna; Faircloth, Susan (The Australian Journal of Indigenous Education, 2016)
We propose the use of an ontological perspective to shift current thinking about the phenomenon of home/school partnerships, particularly through an examination of school leaders (leadership team) — community relationships that seek to better serve Indigenous students and their communities. We reanalysed focus group interviews of indigenous Māori students and their whānau/families from a wider New Zealand study that investigated the development of culturally responsive leadership in 84 secondary schools. The aim of the leadership intervention was to improve school practices and enable Indigenous Māori students to achieve and enjoy educational success as Māori. Reanalysis of interview material revealed categories related to relational being that highlight both opportunities and impediments to authentic relationships between schools and communities and the development of culturally responsive leadership. This paper attempts to create a framework in regards to relational ontology within a broader struggle for transformative praxis and to provide direction for further theoretical and practical investigation within schools.